Preferensi Politik Pengikut Tarekat Qadiriyah Di Majene Dalam Pemilukada Kabupaten Majene Tahun 2011 - Amin Arsyad (Jurnal Adabiyah: Humanities and Islamic Studies, 2014)
The solidness of “tarekat” followers political preference which tends to show their obedience to their teacher in making political choice has made “tarekat” groups often taken as a base of political support by competing candidates  in politica contest, so happens on the “tarekat Qadiriyah” in Majene election 2011. This research is aimed to analyze the political preference formation of “tarekat Qadiriyah” Majene and the reason of their obedience to their teacher’s political will. The research location is “Kabupaten Majene”, West Celebes Province. The research base used is qualitative research with descriptive research analysis. Informer picking technique used is the purposive technique, so the “tarekat Qadiriyah” teacher, group leader, follower, politicians who follow the “tarekat Qadiriyah” is made as informers in this research. Data collection technique is in depth interview, observation, and literature study with qualitative data analysis technique. The “tarekat Qadiriyah” political preference formation in Majene is caused by their relatively opened paradigm to see the connection between religion and politics. That view caused the assumption that the “tarekat” group involvement in politics is a good thing if aimed for something good. The formation of “tarekat Qadiriyah” teacher’s political view in Majene as the political choice maker of the “tarekat” group he leads is based on his interpersonal relationship with the political actor and the judgement on the actor’s performance in supporting the development of the “tarekat” lesson he leads.